Dynamics of chronic heart failure with a low ejection fraction when dapagliflozin is included in standard therapy - A. A. Tsareva; V. A. Razin; S. S. Kosinov (Лечащий Врач)
Objective. The aim of the current research is the dapagliflozin influence on the key parameters that shows the severity of heart failure among patients with chronic heart failure with low ejection fraction.Materials and methods. The research involves 30 mail patients average aged 61,6 ± 11,1. The basis of involving the patients is the following: heart failure with low ejection fraction of any origin and common therapy of chronic heart failure including inhibitors of angiotension converting enzyme/ antagonist of angiotension II receptors, β-blockers, antagonist of mineralocorticoid receptors. The NTproBNP level in blood was defined and there were the transthoracal echocardioscopy with Doppler mapping along with ejection fraction determination according to Simpson, the 6-minute walking test, the questionnaire on health EQ-5D, the Montreal assessment scale of cognitive functions among the heart failure with low ejection fraction patients of the inception cohort and in 6-month period affected by the therapy with SGLT2 inhibitors.Results. The therapy with dapagliflozin has caused the decrease in the NTproBNT level up to 1914,0 ± 500,7 pg/ml, p = 0,001 that 36% less then baseline indexes. There was the increase in ejection fraction of left ventricle by 15,01% comparing with the baseline (35,2 ± 8,6% – baseline, 40,5 ± 10,8% after the SGLT2 inhibitor therapy, p = 0,07). While having 6-minute walking test the significant walking distance increase was found out. It enables us to make the conclusion about the changes of the heart failure functional class according to NYHA from III to II. Analyzing the health status level (according to the questionnaire on health EQ-5D) there was the increase from 56,4 ± 20,4 to 65,8 ± 10,1. According to the Montreal assessment scale there was enhancement of indexes: 24,4 ± 1,6 – baseline, 25,3 ± 1,7 – after the SGLT2 inhibitor therapy, p = 0,34.